Art Effects : Image, Agency, and Ritual in Amazonia - Fausto, Carlos (Book collections on Project MUSE., 2020)
"In Art Effects Brazilian anthropologist Carlos Fausto explores the agency of indigenous artifacts and images in order to offer a new understanding of the pragmatics and ontology of ritual contexts"--